2015
DOI: 10.1038/jhh.2015.37
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the self-management of hypertension: Patients’ experiences of using a mobile phone-based system

Abstract: Globally, hypertension is poorly controlled and its treatment consists mainly of preventive behavior, adherence to treatment and risk-factor management. The aim of this study was to explore patients' experiences of an interactive mobile phone-based system designed to support the self-management of hypertension. Forty-nine patients were interviewed about their experiences of using the self-management system for 8 weeks regarding: (i) daily answers on self-report questions concerning lifestyle, well-being, sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(154 citation statements)
references
References 32 publications
7
135
1
11
Order By: Relevance
“…Effective blood pressure control mitigates these risks but requires diligent patient compliance and involvement in management. mHealth engagement strategies may help support patients in compliance and self-managing their treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Effective blood pressure control mitigates these risks but requires diligent patient compliance and involvement in management. mHealth engagement strategies may help support patients in compliance and self-managing their treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…37 Enrollment in self-management interventions was also negatively influenced by patients' limited knowledge about the pathophysiology of their disease, possible benefits of participating in self-management, and understanding the best self-management behaviors for improving symptom management. 37,44,[46][47][48][49][50][51][52][53] Additionally, patients were less likely to enroll and participate in self-management programs if the content and instructional methods were perceived as too complex or difficult to understand. Interestingly, patients living with cancer reported accessing patient education resources available both online and offline about their condition.…”
Section: Knowledgementioning
confidence: 99%
“…37,54 However, in two studies, patients living with COPD and hypertension reported several positive attitudes toward participating in self-management programs, including the opportunity to learn more about their condition. 50,52 Patients living with various chronic diseases, including cardiovascular disease, chronic lower respiratory conditions, and type 2 diabetes, reported not enrolling, because self-management programs would not teach them anything new and different from what they already learned from their general practitioner. 44,45 Some patients specifically believed that they would not benefit from self-management in any meaningful way as compared to medical or surgical intervention.…”
mentioning
confidence: 99%
“…Uma meta-análise realizada nas bases de dados MEDLINE, Web of Science, EMBASE e Cochrane, com população de 1.978.919, identificou que 59% dos hipertensos aderem ao tratamento medicamentoso, destacando que a baixa adesão está associada ao baixo nível socioeconô-mico, existência de comorbidades e a necessidade de utilizar diversos medicamentos (9) . A presença da baixa adesão ao autocuidado, concomitante a uma alta adesão ao tratamento medicamentoso, condiz com a literatura em relação a ser mais fácil tomar alguns comprimidos diariamente do que mudar o estilo de vida (17) . Outro estudo com pacientes de 50 a 79 anos, também demonstrou que a maioria (59%) dos pacientes entrevistados tinha adesão ao tratamento farmacológico e associou esse resultado à frequência do paciente em consultas com a equipe de saúde, pelo menos uma vez ao ano, a não ingestão de bebidas alcóolicas e a infarto do miocárdio prévio (18) .…”
Section: Introductionunclassified